Cytogenetical and hematological analysis of chronic myelogenous leukemia patients with a novel case 52XX, t (1;9;22) (q23.3; q34; q11.2), +6, +8, i(9) (q10;q10), +18, +19, +21+der22 t(9;22)(q34;q11). Issue 45 (11th November 2022) - Asif, Muhammad; Hussain, Abrar; Ali, Irfan; Baloch, Zarak; Rasool, Mahmood; Achakzai, Niaz M.
Abstract : (9;22) (q34; q11) translocation is appear in above ninety percent of chronic myelogenous leukemia patients while variant/complex translocations were observed in almost 5% to 8% chronic myelogenous leukemia (CML) positive cases. Gleevec (Imatinib Mesylate) is the first choice breakpoint cluster region (BCR)/ABL targeted oral therapy that produced a complete response almost in 71% to 80% of patients affected with CML. A complete blood count (CBC) of 37 patients was done during diagnosis, however only 21 showed abnormal CBC values which were selected for the study. Karyotyping study using bone marrow samples was performed on 21 CML patients for the conformation of 9;22, however, fluorescence in situ hybridisation was performed for the detection of the BCR–ABL fusion gene of 15 patients. Out of 21, 17 patients showed Ph-positive (9;22) (q34; q11) translocation. Sixteen CML patients showed standard translocation however only CML patients showed a three-way variant/complex translocation with six additional chromosomes, 52XX, t(1;9;22) (q23.3;q34;q11), +6, +8, i(9)(q10;q10), +18, +19, +21 + der22 t(9;22)(q34;q11)). Here we report we report a novel case of six additional chromosomes with the three-way translocation of 52XX, t(1;9;22) (q23.3;q34;q11), +6, +8, i(9)(q10;q10), +18, +19, +21 + der22 t(9;22)(q34;q11) in blast phase.